2010
DOI: 10.1016/j.jsb.2010.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Structural fold, conservation and Fe(II) binding of the intracellular domain of prokaryote FeoB

Abstract: FeoB is a G-protein coupled membrane protein essential for Fe(II) uptake in prokaryotes. Here, we report the crystal structures of the intracellular domain of FeoB (NFeoB) from Klebsiella pneumoniae (KpNFeoB) and Pyrococcus furiosus (PfNFeoB) with and without bound ligands. In the structures, a canonical G-protein domain (G domain) is followed by a helical bundle domain (Sdomain), which despite its lack of sequence similarity between species is structurally conserved. In the nucleotide-free state, the G-domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…Prior to our study, several lines of evidence suggested that the Feo proteins may interact to form a functional Feo structure. Interactions among FeoB monomers have been suggested by crystallography studies (51)(52)(53)(54). An interaction between FeoC and FeoB was observed in a BACTH assay for both the V. cholerae (27) and S. enterica (41) proteins.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Prior to our study, several lines of evidence suggested that the Feo proteins may interact to form a functional Feo structure. Interactions among FeoB monomers have been suggested by crystallography studies (51)(52)(53)(54). An interaction between FeoC and FeoB was observed in a BACTH assay for both the V. cholerae (27) and S. enterica (41) proteins.…”
Section: Discussionmentioning
confidence: 94%
“…Further, significant limitations to studying Feo structure by crystallography have been observed, since a consensus on the oligomeric state of FeoB has never been reached. For example, FeoB N-terminal domains from several organisms have crystallized as monomers (35,53,(55)(56)(57) whereas the FeoB N-terminal domains from other organisms have crystallized as dimers or trimers (51)(52)(53)(54). Since those studies used a truncated FeoB protein, interactions involving the membrane-spanning regions or C terminus of FeoB were not detected.…”
Section: Discussionmentioning
confidence: 99%
“…NFeoB consists of a small-GTPase domain (G domain) and a GDP dissociation inhibitor (GDI)-like helical domain. The crystal structures of several forms from E. coli and Klebsiella pneumoniae NFeoB assemble into a funnel-like trimer with a cytoplasmic pore that could facilitate gating and passage of unhydrated ferrous irons (17,18). The G domain exhibits guanosine nucleotide-dependent conformational changes in the Switch I, Switch II, and G5 motifs of the G domain and changes in the distance between G and GDI-like domains.…”
mentioning
confidence: 99%
“…For preparing the holo-FeoC, the protein was purified through the GST column and concentrated aerobically, whereas the follow-up enzyme digestion was performed anaerobically (less than 5 ppm oxygen) in an anaerobic chamber from COY Lab (Grass Lake, MI) and purified through a Superdex-75 10/300 column attached to an ÄKTA purifier (GE Healthcare) inside the anaerobic chamber. Samples were kept at low temperature in a labtop cooler from Nalgene/Sigma-Aldrich (St. Louis, MO 3 and 1% (vol/vol) BME vitamins, as described previously (18,19,21), but with modifications: an additional 50 mg/liter FeCl3 (wt/vol) and 1% (vol/vol) BME vitamins were added to the growth medium. For preparing [U- 13 C, 15 N]-KpFeoC protein, [U-…”
mentioning
confidence: 99%
“…Notably, the structures of NFeoB from several species have been solved (3,11,13,14,19,27). We previously determined the Klebsiella pneumoniae (KpNFeoB) and Pyrococcus furiosus NFeoB crystal structures with and without bound ligands (14).…”
mentioning
confidence: 99%